2002
DOI: 10.1002/1521-3803(20020701)46:4<240::aid-food240>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phospholipid composition of black cumin (Nigella sativa L.) seed oil

Abstract: Black cumin (Nigella sativa L.) seed oil was extracted with two different solvents, n-hexane (H) and a mixture of chloroform/methanol (CM) (2:1, by volume). Amount of total lipid (TL) was higher in the CM miscelle (39.2% of seed fresh weight) than in the H extract (37.9%). Chemical characteristics as well as fatty acid profile of the TL extracts were compared and the analysis revealed that the major fatty acid was linoleic acid C18:2n-6 (ca. 57% of total fatty acid methyl esters (FAME)) followed by oleic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 20 publications
12
57
0
1
Order By: Relevance
“…Moreover, cumin seeds have a substantial amount of some phytosterols such as beta-sitosterol, delta5-avenasterol, and delta7-avenasterol. Cumin has also stigmasterol, campesterol and lanosterol in small amounts [11]. Phytosterols displace cholesterol from intestinal micelles, reducing absorbable cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cumin seeds have a substantial amount of some phytosterols such as beta-sitosterol, delta5-avenasterol, and delta7-avenasterol. Cumin has also stigmasterol, campesterol and lanosterol in small amounts [11]. Phytosterols displace cholesterol from intestinal micelles, reducing absorbable cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…N. sativa seeds are rich in the unsaturated and essential fatty acids. Chemical characteristics, as well as fatty acid profile of the total lipids, revealed that the major unsaturated fatty acid is linoleic acid, followed by oleic acid [17,18,[23][24][25]. The major separate individual phospholipid classes is phosphatidylcholine, followed by phosphatidylethanolamine, phosphatidylserine, and phosphatitdylinisitol, respectively [17,18,26].…”
Section: Ingredients Of N Sativa Seedsmentioning
confidence: 99%
“…Studies were conducted on pharmacological properties of the essential oil of black cumin and thymoquinone on antioxidant activity [4][5][6] and antimicrobial activity [7]. Fixed oil from black cumin is rich in linoleic and oleic acids as well as bioactive phytosterols and tocopherols [8,9].…”
Section: Introductionmentioning
confidence: 99%